STEM STUDENTS’ ENGAGEMENT TO FOSTER INTERNATIONAL MARKETING THROUGH DIGITAL CONTENT - Grāvīte, Vera; Putniņa, Iveta (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
This article aims to find the opportunities how to facilitate the interaction among students, university staff and future students in order to attract more and better students in the field of STEM by sharing students’ digital content on social media. As a potential student group – generation Z are already technology geeks, spend a lot of time on social media, know about the newest technologies and know how to use them it’s crucial to provide content that can impress them as future STEM students with technologies, opportunities, skilled staff and successful alumni. This paper includes the transformation and adjustment of the main aim for each stage, functions, digital content categories and subcategories, as well the interaction level among students, university staff and future students.